Synaptically evoked glutamate transporter currents in Spinal Dorsal Horn Astrocytes - Dougherty Patrick M; Xin Wenjun; Zhang Haijun (SAGE Publishing, 2009)
Abstract Background Removing and sequestering synaptically released glutamate from the extracellular space is carried out by specific plasma membrane transporters that are primarily located in astrocytes. Glial glutamate transporter function can be monitored by recording the currents that are produced by co-transportation of Na+ ions with the uptake of glutamate. The goal of this study was to characterize glutamate transporter function in astrocytes of the spinal cord dorsal horn in real time by recording synaptically evoked glutamate transporter currents. Results Whole-cell patch clamp recordings were obtained from astrocytes in the spinal substantia gelatinosa (SG) area in spinal slices of young adult rats. Glutamate transporter currents were evoked in these cells by electrical stimulation at the spinal dorsal root entry zone in the presence of bicuculline, strychnine, DNQX and D-AP5. Transporter currents were abolished when synaptic transmission was blocked by TTX or Cd2+. Pharmacological studies identified two subtypes of glutamate transporters in spinal astrocytes, GLAST and GLT-1. Glutamate transporter currents were graded with stimulus intensity, reaching peak responses at 4 to 5 times activation threshold, but were reduced following low-frequency (0.1 - 1 Hz) repetitive stimulation. Conclusion These results suggest that glutamate transporters of spinal astrocytes could be activated by synaptic activation, and recording glutamate transporter currents may provide a means of examining the real time physiological responses of glial cells in spinal sensory processing, sensitization, hyperalgesia and chronic pain.